The Evaluation of antioxidant, antimicrobial, and lethality Activities of leaf and bark extract of alnus nepalensis D. Don - Dipak Raj Jaishi; Dinesh Raj Ojha; Indra Ojha; Govinda Bhattarai; Khaga Raj Sharma (Bibechana)
Herbal medicine practitioners have been using folk medicines to treat minor and life-threatening illnesses since ancient times. The main objectives of this research are the estimation of phenolics, flavonoids, and tannins content, antioxidant potential, and different biological activities of plant extracts. Himalayan alder (Alnus nepalensis D. Don), also called Nepalese alder is the most common tree species found in Eastern Himalaya. The ethanolic bark extract showed the highest TPC and TTC which is 300.6 ± 3.12 mg GAE/g and 120.09 ± 3.15 mg TA/g respectively. Methanolic leaf extract showed the highest TFC 137.21 ± 4.67 mg QE/g. In addition to this, ethanolic bark extract exhibited the lowest IC50 17.55 ± 1.17 μg/mL. The methanolic extract of the leaf had the lowest IC50 of 24.03 ± 1.59 μg/mL along with IC50 of standard quercetin 3.43 ± 1.61 µg/mL. Ethanolic bark extract showed good antimicrobial activity against E. coli and K. pneumoniae with zone of inhibition 20 mm and 19 mm respectively which was nearly equal to that of positive control neomycin (28 mm). Furthermore, DCM bark extract had the highest zone of inhibition among all plant extracts which is 21 mm against E. coli. Methanolic leaf extract had significant minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against K. pneumoniae of 0.78 mg/mL and 1.56 mg/mL respectively along with a positive control for MIC and MBC 0.003 mg/mL and 0.007 mg/mL. Ethanolic extract of bark had LC50 80.08 μg/mL and methanolic leaf extract had LC50 468.81 μg/mL. These results show this plant is medicinally important and it could be used as the source of active compounds against infectious diseases in future drug development processes.